Evaluation of reproductive health indicators in women affected by East Azarbaijan earthquake on August 2012 - Farideh Bahmanjanbeh; Shahnaz Kohan; Mohammad Hossein Yarmohammadian; Abbas Haghshenas (Wolters Kluwer Medknow Publications, 2016)
Background: Ignoring reproductive health services during natural disasters leads to some negative consequences such as reduced access to contraceptive methods, sexual disorders, and pregnancy complications. Despite previous researches, there is still more need for research on this area of health. This study attempts to identify the indicators of reproductive health in the women affected by the East Azarbaijan earthquake on August 2012. Materials and Methods: In this descriptive study, reproductive health information pertaining to the years before, during, and after the earthquake were collected and compared in the health centers of the three affected cities including Ahar, Heriss, and Varzaghan as well as the health and forensics centers of the East Azarbaijan province in Iran by census method. Results: Findings indicated a decrease in live birth rate, general marriage fertility rate, stillbirth rate, contraceptive methods coverage, and prevalence of sexually transmitted diseases during and after the earthquake. Moreover, important indicators such as neonatal mortality rate and percentage of infants screened for breast milk, decreased during the disaster year in comparison with the years before and after. Other indicators such as preconception care, pregnancy first visit, rate of caesarian delivery, and under 1-year formula milk-fed infants' percentages increased during the year of disaster in comparison with the years before and after. Conclusions: During the earthquake, some indicators of reproductive health have been reported to decrease whereas some others have gone through negative changes. Despite the partly favorable status of services, decision-makers and health service providers should pay more attention to the needs of women during disasters.